TINJAUAN YURIDIS TERHADAP PERJANJIAN JUAL BELI BENDA BERGERAK (TINJAUAN DALAM SISI PASAL 1458 KUH PERDATA) - Survida Survida (Journal of Law ( Jurnal Ilmu Hukum ), 2016)
ABSTRACTION  In the social life of nation and state that we do not interact much with the activity among humans. Interactions as a social  activity that is complementary and need. Community interaction activities in one of which is the buying and selling of goods. Sale and purchase of goods buy the general publich carried out in the market. These trading activities made in cash or termed “ there is no money stuff “. But buying and selling is a little different when selling goods worth considering. In general, buying and selling is done by the credit agreement. This agreement is done by one person or more or a few people, it could be with an agency or company.The existence of this agreement the parties indirectly tying himself to do his duty and give right to other parties.This study aims to determine the extent to which the validity of the purchase agreement moving object, as well as knowing the legal consuquences purchase agreement moving object when one of the parties or the occurrence of default when buying and selling.The results showed that the agreement in general not tied to any particular shape, but the agreement was binding between one or more persons in an agreement which, when already in communication and get an agreement from the parties buying and selling them and as for the factors supporting the agreement, namely, atapun agreement supporting documents in order to accurrence of an agreement and if one of the parties in default, the party who feels aggrieved is entitled and obliged to demand compensation in both formal and material, atapun cancellation of the agreement either before the witness, atapun front of a jury.In this case both the seller and the buyer must be competent to be buying and selling process both minimize their deeds so that one party default no one harmed when an agreement was happening. Keywords : Sale and Purchase Agreement, the Goods